Treatment of Third Branch Trigeminal Neuralgia With a Balloon Inflated in the Foramen Ovale - Lu, Zhangfan; Wang, Jiadong; Cao, Yang; Sun, Chenglong; Du, Quan; Shen, Yongfeng; Yu, Wenhua; Du, Yuanfeng (Frontiers in Neurology, 2022)
Objective To investigate the efficacy of modified percutaneous balloon compression for simple third branch pain and its postoperative complications. Methods Clinical data and surgical records of 132 patients with third branch pain treated with percutaneous balloon compression from March 2015 to May 2019 were retrospectively analyzed, of which 81 cases were in the modified group and 51 cases were in the classic group. The modified technique was to compress again at the foramen ovale to enhance the compression in V3 after compression of the Gasserian ganglion. Results In the modified group, the overall therapeutic efficiency was 96.3%, with 77 patients (95.1%) having immediate postoperative pain relief and one patient (1.2%) having occasional pain without the need for medication. In the classic group, immediate postoperative pain relief was seen in 43 cases (84.3%), and two patients (3.9%) had occasional pain with no need for medication. The rate of complete pain relief was significantly higher in the modified group than in the classic group (P < 0.05). Postoperative follow-up ranged from 14 to 48 months. The pain-free rates were 77.8 and 54.9% in the modified and classic groups, respectively. The incidence of facial numbness in the region of the first branch was significantly lower than in the classic group (P < 0.001). Conclusion The modified procedure has significant advantages over the classic procedure in improving surgical efficacy, reducing postoperative recurrence rate, and decreasing postoperative numbness in the region, and can be used to treat simple trigeminal neuralgia in the third branch.